(untitled) (Journal of Engineering, 2021)
Plastic soil exhibits unfavorited geotechnical properties (when saturation), which causes negative defects to engineering structures. Different attempts (included various materials) were conducted to proffer solutions to such defects by experimenting in practical ways. On one hand, these attempts aimed to improve the engineering characteristics of plastic soil, and on the other hand, to use problematic waste materials as a stabilizer, like cement kiln dust, and to reduce environmental hazards. This paper explored the shrinkage, plasticity, and strength behavior of plastic soil enhanced with cement dust. The cement dust contents were 0%, 5%, 10%, 15% and 20% by dry weight of soil. An experimental series of shrinkage and plasticity tests and unconfined compression tests were carried out to explore the effects of cement dust on the quantitative amount of shrinkage, plasticity characteristics, and shear strength experienced by plastic soil. The effects of curing on soil strength were also investigated. The finding of this paper showed that the critical behavior and plasticity of plastic soil could be reduced by mixing the soil with 15% or 20% of cement dust. The undrained shear strength, cu, of plastic soil-cement dust mixtures increased with the increasing dust content up to 20%. In fact, this strength was affected by the curing period. The best enhancement was attained when the content of cement dust was 20%, and the undrained shear strength was increased more than three times at this content.